Rubber technologist's handbook. Volume 2 - White, J. R., 1943-; De, Sadhan K.; Naskar, K. (ISmithers Rapra, 2009)
Annotation This book is a companion volume to Rubber Technologist's Handbook published in 2001. Written by experts in their respective fields, this handbook discusses the most recent developments in the subject. The ten chapters cover Microscopic Imaging of Rubber Compounds, Intelligent Tyres, Silica-Filled Rubber Compounds, Fibres in the Rubber Industry, Naval and Space Applications of Rubber, Advances in Fillers for the Rubber Industry, Thermoplastic Elastomers by Dynamic Vulcanisation, Polymers in Cable Applications, Durability of Rubber Compounds, and Radiochemical Ageing of Ethylene-Propylene-Diene Monomer. This book will serve the needs of those who are already in the rubber industry and new entrants to the field who aspire to build a career in rubber and allied areas. Materials Science students and researchers, designers and engineers should all find this handbook helpful.
Keywords: Rubber industry and trade.; Rubber.; elektronické knihy; electronic books